Prognostic value of programmed cell death ligand-1 expression in breast cancer: A meta-analysis. Issue 49 (4th December 2020) - Zhang, Yingzi; Tian, Jiao; Qu, Chi; Tang, Zhenrong; Wang, Yu; Li, Kang; Yang, Yuan; Liu, Shengchun
Abstract: Background: The correlation between programmed cell death-ligand 1 (PD-L1) which may affect T cell to form the immune tolerance and breast cancer (BC) still maintains to be uncovered. This meta-analysis was about to explore PD-L1 expression as well as its prognostic role in BC. Methods: First of all, we performed 3 databases: PubMed, Embase, and Web of Science to explore publications between January of 2015 and January of 2020. Strict inclusion and exclusion criteria were conducted: immunohistochemistry shall be used to detect target molecule expression and at least 1 survival indicator and related data we need should be included. The hazard ratio and 95% confidence interval were pooled related with survival as well as clinicopathological parameters. The effects of PD-L1 in differed aspects like sample size and age of each cohort were demonstrated by subgroup analyses as well as sensitivity analyses which may complain the potential source of heterogeneity. P  < .05 indicates factors were charge of the heterogeneity of prognosis. Begg and Egger tests were used to identify publication bias. Results: We identified 12 studies containing a blanket of 4336 patients with BC for whom PD-L1 positive tumor cells were related with higher tumor stage, lymph node metastasis, estrogen receptor negativity, human epidermal growth factor receptor 2 positivity, luminal B and triple negative BC molecular subtype and high nuclear-associated antigen Ki- 67 expression. Meanwhile, compared to patients with PD-L1 negative expression, PD-L1 positivity associated with worse overall survival (Hazard ratio [HR]:1.43; 95% CI:0.98–2.10; P  < .001) and might have no obvious tight connection with disease free survival (HR:1.40; 95% CI:1.11–1.78; P = .101) and recurrence free survival (HR:2.36; 95% CI:1.04–5.34; P  = .145). The outcome of the meta-analysis was confirmed to be credible by sensitivity analysis. Publication bias was not existed indicated ( P  = .640). Conclusion: Positive PD-L1 expression has a worse clinical outcome in patients with BC demonstrated by our meta-analysis. Being urgent to catch attention to the role of PD-L1 in BC, it may be considered as prognostic marker of immune microenvironment for improving therapy efficacy. Abstract : Supplemental Digital Content is available in the text